MEWUJUDKAN KEPASTIAN HUKUM, KEADILAN DAN KEMANFAATAN DALAM PUTUSAN HAKIM DI PERADILAN PERDATA - FenceM Wantu (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Courts’ verdicts issued by the judge ideally contain aspects of legal certainty, justice, and utility. It is not easy though to synergize the three aspects aforementioned. Between aspects of legal certainty and justice, in particular, there are always disagreements. The research results conclude that a judge does not have to stick on one principle whenever examining and deciding a case. In terms of obstacles, the judge is facing a deadlock whenever written stipulations cannot answer the problems arose. The emphasis on justice principle means that the judge should take into consideration the law, which exists in the society, including customs and unwritten laws. The judge in his argument and legal consideration must be able to accommodate any stipulations exist in the society, both customs and unwritten law. The emphasis on utility principle tends to direct to an economic nuance circumstance. It bases its thought on the idea that law is for human beings or public. Key words: legal certainty, justice, utility, civil justice